Comparison of Misoprostol and Dinoprostone for Induction of Labour in Full Term Pregnancy - Khan, Sara; Anwar, Sadia; Gul, Fatima; Riaz, Humaira (Indus Journal of Bioscience Research, 2025)
Background: Labor induction is a common obstetrical practice, and a number of agents are effective in facilitating the process. Misoprostol and dinoprostone are two common medications, and their comparative effectiveness regarding labor length and success rate is a subject of continued investigation. Objective: To compare the efficacy of misoprostol and dinoprostone for labor induction at term. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from September 2024 to March 2025 at the Department of Obstetrics and Gynaecology, MTI-D.I. Khan. Methodology: 152 pregnant women were randomized into either the dinoprostone (Group B) or misoprostol (Group A) group, with an even split of participants in both groups of 76 each. Inclusion in the study was women presenting between the ages of 18 and 40 years, having a singleton gestation at term (39 weeks of gestation), intact amniotic membrane, and Bishop score ≤6. Induction of labor using either dinoprostone or misoprostol was conducted, and labor duration and success rate of vaginal delivery were noted. Results: Misoprostol demonstrated superior performance with a 75.0% success rate, compared to dinoprostone's 47.4% (p<0.001). Additionally, labor duration was significantly shorter in the misoprostol group, with an average of 10.66 ± 2.81 hours, compared to 13.84 ± 2.37 hours for dinoprostone. Stratified analysis revealed that misoprostol was particularly more effective in younger patients (≤30 years), as well as in those with fewer previous births and lower socioeconomic status. Conclusion: Misoprostol is a more effective and time-efficient agent for labor induction compared to dinoprostone.